Optimizing Roof Truss Installations With Body-Loaded Photoelastic Models (4e512a82-75d6-4685-98e3-857d3836994b) - Neall. George M. (Society for Mining, Metallurgy & Exploration, 1977)
No method of roof control yet devised has proven to be universally acceptable for the wide range of strata conditions experienced in U.S. coal mines. However, a relatively new innovation, the roof truss, has proven itself capable of preventing roof failures which both conventional and resin bolting could not. Presently, the economics of roof trusses are not favorable when compared to bolting due primarily to drilling and installation procedures, but this is expected to change with improved truss and equipment designs. To realize the full potential of this new method of roof control, design criteria are needed which can optimize the effect of the truss for varying strata conditions. A review of the literature reveals that some work has been conducted on the roof truss. 1 Gambrell and Haynes (1970) showed that the roof truss is superior to angled roofbolts installed through a header. Sheorey, Verma, and singh2 (1973) used statics to prove that the optimum angle of inclination should be greater than 450? However, to date, no systematic attempt has been made to establish design criteria. In this report, the problem was approached in three ways. First, model studies were performed to determine general trends of truss support as a function of a number of variables. This provided a better understanding of the support mechanism involved. Secondly, beam theory was employed to calculate the actual support capacity of a truss, realizing the many simplifications, assumptions, and shortcomings of this approach to such a complicated problem. Last, field testing will be utilized to test the hypotheses previously developed and provide hard data to further synthesize roof truss design criteria. Field testing has recently commenced and should be complete before mid 1977.